Théâtre Jeunesse between France and Italy: editorial Experiences (Itinera, 2019)
Our analysis compares French and Italian theatre for young people, and focuses on differences between the two, especially when it comes to publishing plays for young audience. While France has been supporting the publication of plays for young audiences since the late 1980s, involving a growing number of publishing houses, Italy is still showing modest interest in publishing plays for young people, as our investigation shows.